Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1373/clinchem.2011.172759
|View full text |Cite
|
Sign up to set email alerts
|

9p21 and the Genetic Revolution for Coronary Artery Disease

Abstract: BACKGROUND It has long been recognized that 50% of the susceptibility for coronary artery disease (CAD) is due to predisposing genetic factors. Comprehensive prevention is likely to require knowledge of these genetic factors. CONTENT Using a genomewide association study (GWAS), the Ottawa Heart Genomic Study and the deCODE group simultaneously identified the first genetic risk variant, at chromosome 9p21. The 9p21 variant bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 73 publications
0
41
0
1
Order By: Relevance
“…35 The pattern of pleiotropic associations suggests a hypothesis that cells responsible for maintaining the integrity of the arterial wall may mediate both atherosclerotic and nonatherosclerotic diseases. 363,364 Although this hypothesis is the leading hypothesis tying these observations at the population level together, it remains to be proven.…”
Section: The 9p21 Susceptibility Locus and Insights Into The Role Of mentioning
confidence: 99%
“…35 The pattern of pleiotropic associations suggests a hypothesis that cells responsible for maintaining the integrity of the arterial wall may mediate both atherosclerotic and nonatherosclerotic diseases. 363,364 Although this hypothesis is the leading hypothesis tying these observations at the population level together, it remains to be proven.…”
Section: The 9p21 Susceptibility Locus and Insights Into The Role Of mentioning
confidence: 99%
“…In fact, the average MAF was considerably higher for SNPs in the noncoding regions (20%-25%) than in the coding regions (12%-16%) [30], making it difficult to pick them up in our rather small-sized cohort. A recent review of GWAS suggests that more than 70% of genetic variants identified to date for CAD are located in the noncoding regions [31].…”
Section: Discussionmentioning
confidence: 99%
“…This area addresses multiple topics, including cardiovascular sequencing, transcriptomics, and epigenetics (18 ); general genomics (19 ); 9p21 (20 ); metabolomics (21 ); and PCSK9 and LDL cholesterol responses from the JUPITER trial (22 ).…”
Section: 5mentioning
confidence: 99%